Stock market screening: An analogical study on conventional and shariah-compliant stock markets - Zandi, Gholamreza Reza; Abdul Razak, Dzuljastri; Hussin, Nur Hidayah (Canadian Center of Science and Education, 2014)
enchmarking Shariah-Compliant stocks listed in Bursa Malaysia, this paper examined whether the stocks which are approved by SACSC are also considered as Shariah-Compliant under International Indices. 35 top Shariah-Compliant stocks listed in Bursa Malaysia were examined against four stock screening criteria of DJIM, MSCI, FTSE and S&P. Due to the differences in stock screening criteria, the factors evaluated that lead to variances in Shariah-Compliant status for a particular stock. The results from the test indicate that Shariah-Compliant stocks listed in Bursa Malaysia are not necessarily Shariah-Compliant stocks in the four Indices of DJIM, MSCI, FTSE and S&P. The high debt and low market capitalization are the main factors of dropping the Malaysian Shariah-Compliant stocks by the four Indices. The three stages of screening which carry the most Islamic stock screening process include screening on industry, income statement and balance sheet.